Health information-seeking behavior among users of traditional, complementary and integrative medicine (TCIM) - Miriam Trübner; Alexander Patzina; Judith Lehmann; Benno Brinkhaus; Christian S. Kessler; Rasmus Hoffmann (BMC Complementary Medicine and Therapies)
Abstract Background The use of traditional, complementary, and integrative medicine (TCIM) is widespread among the German population and driven by various motives, including both supplementing and avoiding treatments with conventional medicine. The aim of this article is to examine how these motives relate to different health information-seeking behaviors. Methods The study uses regression analysis based on data from a German online access panel, which explored the use and acceptance of TCIM in Germany in 2022. From this study, we use information on 1,696 individuals (aged 18–75 years) who vary in their motives for using TCIM (subjective statements on five-point Likert scales) and have used TCIM to treat health problems. Results Overall, TCIM is considered more a health-promoting measure than it is driven by aversion towards conventional medicine. Our analysis of information-seeking behavior for certain therapeutic procedures reveals that, as respondents’ propensity to use TCIM as a health-promoting measure rises, they are more likely to perceive themselves as being influenced by scientific studies (AME: 0.04, p = 0.004), personal advice (AME: 0.09, p = 0.000), and their social circle’s experiences (AME: 0.08, p = 0.000). In contrast, respondents who use TCIM more due to aversion to conventional medicine are less likely to perceive themselves as being influenced by scientific studies (AME: -0.04, p = 0.004) and doctors (AME: -0.07, p = 0.000). When analyzing respondents’ most important medical information source, our results reveal that the more individuals indicate using TCIM out of aversion, the more likely they are to consider (online) media outlets their most important medical resource (AME: 0.05, p = 0.000), while the likelihood of considering medical professionals most important decreases (AME -0.06, p = 0.000). Conclusion Motives behind TCIM use vary and correspond to differences in individuals’ health information-seeking behavior. Beyond these motive-related differences, TCIM users value sources of health information other than their medical practitioners. This calls for an intensification of TCIM training among medical professionals to provide high-quality consultation and the creation of reputable online portals to ensure the provision of trustworthy information about TCIM.